The positive impact of transit-oriented-development characteristics on Metro Station usage: A case study of Tehran's metro stations and TOD index calculation - Khosravi, Hossein; Abrishami, Motahareh; Mehrian, Majid Ramezani; Chamberlain, Brent (Cities, 2024)
Transit-Oriented Development (TOD) facilitates the creation of more walkable cities. To implement TODs, urban planners need a mechanism to delineate TOD levels so they can envision future planning trajectories. This study offers an approach to developing scores for TODs within Tehran, a metropolitan area with metro stations and Bus Rapid Transit that facilitate public transportation usage. TODs exhibit distinct characteristics when compared to other areas within a city. Furthermore, TODs vary in their levels of integration across transit, commerce, and residential, necessitating policies specific to each TOD. The main objective is 1) To identify the factors that best define TODs for metro stations and 2) To develop a TOD index to measure the TOD score. We used three different spatial units of measurement to define a range of metrics to identify how effective TODs work with different characteristics. The spatial units include: 1. Thiessen polygons 2. the walkable distance of the transit nodes and 3. Thiessen polygons without the walkable distances. The main criteria we used are travel behavior, walkability, accessibility, transportation inclusivity, network attribute, trip generation rate, and land use. The metrics are weighted based on the correlation results with the usage rate. A Negative Binomial regression was developed to find the metrics that are significantly influential on the usage rate of the metro stations. Results indicate that all criteria except the land use are significantly correlated with the usage rate of metro stations. •The study focused on Transit-Oriented Development (TOD) in Tehran.•TODs exhibit distinct characteristics and varying levels of development, necessitating tailored policies for each location.•The study identifies key factors that define TODs for metro stations in Tehran.•Three different spatial units of measurement are used to assess TODs.•Correlation analysis shows that all criteria except land use are significantly correlated with the usage rate of metro station.